PENERAPAN FUZZY GOAL PROGRAMMING DALAM PENGOPTIMALAN PERENCANAAN PRODUKSI - Clarine Alfiani; Melyatul Zavina; Uswatun Khasanah; Muhammad Nur Fadli; Annisa Indahsari (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
Production planning is a very important activity for companies in considering production factors ranging from the number of products that must be produced, when the product must be completed, and other things needed. Improper production planning risks causing losses to the company because the use of production costs and profit estimates are not optimized. One method that can be used in optimizing production planning is the fuzzy goal programming method. Fuzzy goal programming is an extension of linear programming that can solve problems of more than one goal in the presence of target constraints. This study aims to examine and apply the fuzzy goal programming method which is solved by the simplex method in Ayune Kitchen production planning by maximizing revenue and minimizing raw material costs. The data used in this study include product data (comb bread, dulce, brulee, mentai, lasagna, and briyani rice), production prices, and raw materials for making products from Ayune Kitchen which will be analyzed using linear programming and fuzzy goal programming methods. simplex. The result of this research is the optimal income that will be obtained by Ayune Kitchen is Rp. 8.830.000 and the optimal expenditure incurred by Ayune Kitchen to purchase raw materials is Rp. 6.687.821